Beyond the distinction between incumbency and opposition: Retrospective voting at the level of political parties. (November 2019) - Stiers, Dieter
Retrospective voting is one of the most frequently investigated theories of voting behaviour. It postulates that voters punish or reward incumbent parties according to their performance. This approach, however, cannot explain why voters cast a stable opposition vote, or switch between incumbent parties or opposition parties, respectively. This study fills this gap by showing that this traditional view should be complemented with the approach of retrospective voting to work at the level of political parties – irrespective of their incumbency status. Using the data of the second module of the Comparative Study of Electoral Systems, it provides the first large-scale test of this new perspective on electoral accountability. The results show that satisfaction with the previously endorsed party is an important determinant of the current party choice, and that it is so for voters for all parties alike. These results provide a theoretical foundation for party switches that could not be explained by the traditional model.